1365Does pain self-efficacy influence initial bending following exercise in adults with chronic low back pain?. (2nd September 2021) - McManus, Fiona; Pranata, Adrian; Simpson, Julie A.; Farragher, Joshua; Crofts, Samuel; Wu, Wen; Bryant, Adam
Abstract: Background: Differences in pain self-efficacy between individuals with chronic low back pain (CLBP) may partly explain why response to exercise varies. The aim of this study was to determine if pain self-efficacy influences initial forward bending following an exercise intervention in adults with CLBP. Methods: A total of 69 adults (18-65 years old) with moderate-severe CLBP-related disability who presented to a primary care physiotherapy clinic in Melbourne, Australia underwent baseline assessment of pain self-efficacy, pain intensity and kinesiophobia, prior to participation in one of two 12-week exercise interventions. Two outcome measures (lumbar and hip flexion range of motion (ROM) over the first quarter of forward bending from stance), were assessed at baseline, 6 and 12-weeks. Multiple linear mixed-effects modelling was performed for each outcome measure. Results: For every 10-point increase in baseline pain self-efficacy, lumbar flexion ROM during initial bending decreased by an estimated mean 0.51 (95% CI: -1.41, 0.39) and 0.94 (95% CI: -1.75, -0.13) degrees at 6 and 12-weeks, respectively. Similarly, hip flexion ROM during initial bending decreased by an estimated mean 1.64 (95% CI: -3.70, 0.41) and 1.43 (95% CI: -3.34, 0.48) degrees at 6 and 12-weeks, respectively, per 10-point increase in baseline pain self-efficacy. Conclusions: Pain self-efficacy did not influence initial forward bending following a 12-week exercise intervention. As the exercises were not targeted to improve bending, further research is required to verify these findings. Key message: Pain self-efficacy may not explain variations in initial forward bending following an exercise intervention in adults with CLBP.